Štátne výchovno-vzdelávacie programy predprimárnej edukácie Slovenskej republiky a Maďarska - Borbélyová Diana (DISPUTATIONES SCIENTIFICAE UNIVERSITATIS CHATHOLICAE IN RUZOMBEROK, 2022)
The education policies of the European Union countries have their own specificities and differences. These differences can be seen not only in direct educational activities, but also in the legislatively binding curriculum documents for pre-primary education. The present study deals specifically with the comparison of the State Curriculum for Pre-primary Education in Kindergartens 2016 (Slovak Republic) and the National Education Programme 2012 (Hungary).